2023
DOI: 10.3390/ijms241813899
|View full text |Cite
|
Sign up to set email alerts
|

Paying Comprehensive Attention to the Temperature-Dependent Dual-Channel Excited-State Intramolecular Proton Transfer Mechanism of Fluorescence Ratio Probe BZ-DAM

Jiaan Gao,
Yifu Zhang,
Hongyan Mu
et al.

Abstract: The mechanism of fluorescence detection of diethyl chlorophosphate (DCP) based on 2-substituted benzothiazole (BZ-DAM) was studied by a theoretical calculation method. It should not be ignored that both the BZ-DAM and the detection product BZ-CHO have two excited-state intramolecular proton transfer (ESIPT) channels. Density functional theory (DFT) and time-dependent DFT (TDDFT) theory were used to study the photophysical mechanism of two compounds in two channels in (acetonitrile) ACN solvent, and the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Excited-state intramolecular proton transfer (ESIPT) is a photophysical process that promotes the interconversion isomerisation between enol and keto in molecules under photoexcitation [17][18][19][20][21]. Because of the significant Stokes displacement emission of the ESIPT process [22,23], it has been extensively used in organic luminescent materials, fluorescent probes, biosensors, molecular light switches and other fields [24][25][26][27][28]. As early as the 1950s, Weller et al demonstrated that methyl salicylate had ESIPT characteristics and proposed a mechanism of molecular isomerisation leading to double fluorescence [29].…”
Section: Introductionmentioning
confidence: 99%
“…Excited-state intramolecular proton transfer (ESIPT) is a photophysical process that promotes the interconversion isomerisation between enol and keto in molecules under photoexcitation [17][18][19][20][21]. Because of the significant Stokes displacement emission of the ESIPT process [22,23], it has been extensively used in organic luminescent materials, fluorescent probes, biosensors, molecular light switches and other fields [24][25][26][27][28]. As early as the 1950s, Weller et al demonstrated that methyl salicylate had ESIPT characteristics and proposed a mechanism of molecular isomerisation leading to double fluorescence [29].…”
Section: Introductionmentioning
confidence: 99%